Short‐term FSH treatment and sperm maturation: a prospective study in idiopathic infertile men. (15th March 2017) - Casamonti, E.; Vinci, S.; Serra, E.; Fino, M. G.; Brilli, S.; Lotti, F.; Maggi, M.; Coccia, M. E.; Forti, G.; Krausz, C.
Summary: The standard FSH treatment is based on a 3 months period, after which both quantitative/qualitative improvement of sperm parameters and increased pregnancy rate were reported. In this prospective clinical trial, for the first time, we studied (i) Sperm hyaluronic acid binding capacity after highly purified FSH (hpFSH) treatment; (ii) the effect after short‐term and standard treatment on this functional parameter. As secondary objective, we analyzed three SNPs on FSH β and FSHR genes to define their potential predictive value for responsiveness. From a total of 210 consecutive patients, 40 oligo‐ and/or astheno‐ and/or teratozoospermic patients fulfilled the inclusion criteria. Treatment consisted in hpFSH 75 IU/L every other day for 3 months. To avoid potential biases derived from the lack of placebo, we analyzed each patient after 4–6 months of 'wash‐out' period. After FSH treatment, we observed a statistically significant ( p  < 0.001) improvement of the percentage of hyaluronic acid bound spermatozoa from basal to T1 (after 1 month) and to T3 (after 3 months). Importantly, these values returned to near‐baseline value after the wash‐out. The same results were detected for total motile sperm count after 3 months with return to baseline after wash‐out. Forty‐two percent of patients responded to the therapy with increasing hyaluronic acid binding capacity above the double of the Intraindividual Variation (IV) while 24% of patients reached above the normal Sperm‐Hyaluronan Binding Assay (HBA) value. Further increase in 'responders' was observed at T3. The responsiveness to treatment resulted independent from FSHR/FSH β polymorphisms. The significant positive effect on sperm maturity after 1 month opens novel therapeutic perspectives. In view of both the high cost and the relative invasiveness of treatment, the short protocol (1 month) could represent a viable FSH treatment option prior Assisted Reproductive Techniques since FSH, by acting on sperm maturation, increases the proportion of functionally competent cells.